2007
DOI: 10.1080/10826070701589016
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Densitometric Determination of 6‐Gingerol and 6‐Shogaol in some Commercial Gingers (Zingiber OfficinaleRoscoe)

Abstract: A simple and rapid densitometric method has been developed for determination of 6-gingerol and 6-shogaol in some commercial gingers. After extracting the samples four times with methanol, the solutions were spotted on pre-coated silica gel tlc plates, which were eluted with a mixture of n-hexane-ethyl ether (4:6, v/v). Quantitative evaluation was performed by measuring the absorbance reflectance of the analyte spots at l ¼ 577 nm after sprayed with anisaldehyde-h2so4 reagent. The tlc-densitometric method is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Recovery studies were performed by the method of standard addition and this method showed the excellent reliability and reproducibility with recovery values from 99.79 to 99.84%. Melianita et al (2007) developed a rapid as well as a simple densitometric method for determination of [6]-gingerol and [6]-shogaol, which can be used for routine analysis of ginger samples in herbal drugs industry quality control laboratories.…”
Section: Gc-ms Analysis Of Volatile Compoundsmentioning
confidence: 99%
“…Recovery studies were performed by the method of standard addition and this method showed the excellent reliability and reproducibility with recovery values from 99.79 to 99.84%. Melianita et al (2007) developed a rapid as well as a simple densitometric method for determination of [6]-gingerol and [6]-shogaol, which can be used for routine analysis of ginger samples in herbal drugs industry quality control laboratories.…”
Section: Gc-ms Analysis Of Volatile Compoundsmentioning
confidence: 99%
“…Many quantitative methods have been applied to the analysis of gingerols (Bhattarai, Tran, and Duke 2001;Lee et al 2007;Melianita et al 2007;Rai et al 2006;Schwertner and Rios 2007;Wang et al 2002). Among these methods, HPLC has been considered to be a powerful tool for determination of gingerols in ginger.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our work on standardization of Ayurvedic formulations [23], we planned to evaluate 6-gingerol in this formulation and in market and Suprabha ginger, a variety of ginger is cultivated in Patangi of Koraput district, Orissa. Many TLC and HPTLC methods have been reported for quantitative analysis of 6-gingerol in ginger [24][25][26]. Moreover, the HPTLC method described in this paper is inexpensive, rapid, and more sensitive than previously reported methods.…”
Section: Introductionmentioning
confidence: 91%